Numerical and Experimental Investigations on Robust Output Feedback Control for Active Vibration Attenuation of Flexible Smart System - Arun P. Parameswaran; Anjan N. Padmasali; K. V. Gangadharan (IEEE Access, 2023)
This paper investigates the prototyping and implementation of an output feedback-based robust controller on a Field Programmable Gate Array (FPGA) platform. The Smart System under Test (SSuT) in this submission is a flexible cantilever beam bonded with Piezoelectric (PZT 5H) patches that act as a sensor as well as an actuator (perturbance creation as well as control actuation). For ease of modeling and subsequent controller design in the laboratory studies, the low-frequency dynamics of the smart system are approximated to only a Single Degree of Freedom (SDOF) in terms of flexural vibrations. The SSuT is modeled analytically through finite element modeling and experimentally through sub-space system identification process. The developed models’ accuracy is compared with the experimental results of non - parametric modeling. The developed models are then used to conduct the simulation studies with the designed robust output feedback controller in the closed loop. Apart from the simulation studies, the designed controller was also prototyped on an FPGA platform using LabVIEW FPGA with the associated hardware in loop to carry out the experimental validation of its performance. The robustness and efficiency of the prototype controller to control the system vibrations in real-time were proved through extensive tests at single resonant frequencies and a range of frequencies encompassing the dominant resonant regions in the flexural mode. Findings from this study are further used to ensure satisfactory active vibration control of smart cantilever systems in various heavy/aerospace industries by approximating them to suitable benchmark systems in the laboratory.